Measurement and analysis of direct and indirect household energy consumption: a case study of China - Tang, Zhaoxi; Chen, Liping (Frontiers in Energy Research, 2023)
Household energy consumption is one of the important indicators reflecting the economic development and living standard across countries. Using China's classified household energy consumption and daily expenditure data from 2011 to 2019, this paper first calculated the overall direct and indirect household energy consumption in China in recent years by means of energy classification and consumer lifestyle analysis (CLA), and then analyzed the characteristics and changes of household energy consumption structure, and the different trends between urban and rural areas in China. We found that (1) Coal consumption occupied the first place in indirect energy consumption, followed by electricity. In terms of the overall trends, whether direct or indirect energy consumption, the proportion of coal was declining while those of electricity and natural gas were increasing year by year. (2) Indirect energy consumption accounted for the majority of the total, and the largest share of that was about housing consumption both in urban and rural areas. The changes in the indirect energy consumption structure of the urban and the rural were quite different. Compared with the indirect energy consumption of the rural, that of the urban showed both a faster growth rate and a larger share in the total indirect consumption, which reflected the inequality trend at present in energy consumption intensity and structure between urban and rural areas in China.